+0  
 
0
244
1
avatar

How does this (-x -6) / (x2 + 3x)

Simplify to: 1/(x+3) - (2/x)

Guest Aug 6, 2017
 #1
avatar+26814 
0

y = (-x-6)/(x2+3x) 

 

y = (-x-6)/(x(x+3))

 

Use partial fraction expansion:

 

y = A/x  +  B/(x+3)

y = (A(x+3) + Bx)/(x(x+3)) → ((A+B)x + 3A)/(x(x+3))

 

For the two sets of y to be the same we must have:

 

3A = -6  so  A = -2

 

A + B = -1

-2 + B = -1 so B = 1

 

Hence y = -2/x + 1/(x+3)

.

Alan  Aug 6, 2017

22 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.